Endovascular repair for thoracoabdominal aortic aneurysms: current status and future challenges - Tenorio, Emanuel R.; Dias-Neto, Marina F.; Lima, Guilherme Baumgardt Barbosa; Estrera, Anthony L.; Oderich, Gustavo S. (Annals of Cardiothoracic Surgery, 2021)
Open surgical repair has been the gold standard for treatment of thoracoabdominal aortic aneurysms (TAAA). Currently, open surgical repair has been reserved mostly for young and fit patients with connective tissue disorders, using separate branch vessel reconstructions instead of ‘island’ patches, and distal perfusion instead of a ‘clamp and go’ technique. Endovascular repair has gained widespread acceptance because of its potential to significantly decrease morbidity and mortality. Several large aortic centers have developed dedicated clinical programs to advance techniques of fenestrated-branched endovascular aortic repair (FB-EVAR) using patient-specific and off-the-shelf devices, which offers a less-invasive alternative to open repair. Although FB-EVAR was initially considered an option for older and frail patients, many centers have expanded its indications to any patient with suitable anatomy and no evidence of connective tissue disorders, independent of their clinical risk. In this article, we review current techniques and outcomes of endovascular TAAA repair.